The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10517-008-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the liver of mice infected with avian influenza virus subtype H5N1

Abstract: Intranasal infection of male outbred rats with isolate of influenza A virus subtype H5N1 (A/Gs/Krasnoozerskoye/627/05) from the Novosibirsk region was followed by high mortality of experimental animals. Morphological study of liver samples revealed subtotal destructive changes in the liver parenchyma (proteinosis and centrolobular necroses), which was related to hemodynamic disorders and cytokine dysregulation. The decrease in reparative activity of hepatocytes was probably followed by hepatocellular failure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Some studies have shown that IAVs of many subtypes (H1N1, H5N1, and H7N9) not only cause lung infection but also impair multiple extrapulmonary tissues and organs, such as the brain, heart, thymus, pancreas, liver, spleen, adrenal glands, kidneys, ovaries, and fallopian tubes. The resulting diseases and disorders include encephalitis, myopericarditis, thymus atrophy, pancreatitis, diabetes, subtotal destructive changes in the liver, spleen atrophy, and acute kidney damage 3‐9 . Certain components of IAVs, such as the NP antigen and RNA, were also found in these organs 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that IAVs of many subtypes (H1N1, H5N1, and H7N9) not only cause lung infection but also impair multiple extrapulmonary tissues and organs, such as the brain, heart, thymus, pancreas, liver, spleen, adrenal glands, kidneys, ovaries, and fallopian tubes. The resulting diseases and disorders include encephalitis, myopericarditis, thymus atrophy, pancreatitis, diabetes, subtotal destructive changes in the liver, spleen atrophy, and acute kidney damage 3‐9 . Certain components of IAVs, such as the NP antigen and RNA, were also found in these organs 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…This dysregulation makes a significant contribution to the high mortality of H5N1 influenza(Cheung et al, 2002 ; de Jong et al, 2006 ; Us, 2008 ; Cillóniz et al, 2009 ; Tisoncik et al, 2012 ). In addition to the respiratory systems, IAV infection can also affect other organs of the digestive and nervous systems including the spleen, liver, small intestine and brain(Leon'teva et al, 1989 ; Sharkova et al, 2008 ; Chaves et al, 2014 ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%